PENGARUH STRATEGI APLIKATIF PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP SIKAP WAJIB PAJAK HOTEL DI KOTA SURAKARTA - Ririk Yunita HKS (MANAJEMEN DAN KEUANGAN, 2006)
This research which is committed to hotel tax payer at City of Surakarta, has a purpose to analyze the influence of tax collecting by Dispenda Surakarta to the attitude of hotel tax payer. The method used in this reserach is random sampling from 6 (six) star hotels, and 44 (forty four) melati hotels as respondens who represent its population. The analysis equipment used in this research are Multiple Regression, t test, F test, and Coefficient of Determination. All data has passed Validity and Reliability test before examined with the methods above. This research concludes that site observation strategy and incentive sharing policy has negative influence to the attitude of hotel tax payer, when the bill print restitution strategy and task force audit team strategy have positive influence. The most dominant variable is task force audit team strategy. The variables outside thus research models has bigger influence (54,40%). So it is important to perform evaluation to those variables. It seems that Dispenda Surakarta needs to improve more socialization and implementation quality of each hotel tax collection strategy at Surakarta.